Enhanced Performance of Perovskite Single-Crystal Photodiodes by Epitaxial Hole Blocking Layer - Pan, Yuzhu; Wang, Xin; Xu, Yubing; Li, Yuwei; Elemike, Elias Emeka; Shuja, Ahmed; Li, Qing; Zhang, Xiaobing; Chen, Jing; Zhao, Zhiwei; Lei, Wei (Frontiers in Chemistry, 2020)
Introducing hole/electron transporting and blocking layers is considered to enhance the performance of electronic devices based on organic–inorganic hybrid halide perovskite single crystals (PSCs). In many photodiodes, the hole/electron transporting or blocking materials are spin-coated or thermal-evaporated on PSC to fabricate heterojunctions. However, the heterojunction interfaces due to lattice mismatch between hole/electron, transporting or blocking materials and perovskites easily form traps and cracks, which cause noise and leakage current. Besides, these low-mobility transporting layers increase the difficulty of transporting carriers generated by photons to the electrode; hence, they also increase the response time for photo detection. In the present study, MAPbCl3-MAPbBr2.5Cl0.5 heterojunction interfaces were realized by liquid-phase epitaxy, in which MAPbBr2.5Cl0.5 PSC acts as an active layer and MAPbCl3 PSC acts as a hole blocking layer (HBL). Our PIN photodiodes with epitaxial MAPbCl3 PSC as HBL show better performance in dark current, light responsivity, stability, and response time than the photodiodes with spin-coated organic PCBM as HBL. These results suggest that the heterojunction interface formed between two bulk PSCs with different halide compositions by epitaxy growth is very useful for effectively blocking the injected charges under high external electric field, which could improve the collection of photo-generated carriers and hereby enhance the detection performance of the photodiode. Furthermore, the PIN photodiodes made of PSC with epitaxial HBL show the sensitivities of 7.08 mC Gyair−1 cm−2, 4.04 mC Gyair−1 cm−2, and 2.38 mC Gyair−1 cm−2 for 40-keV, 60-keV, and 80-keV X-ray, respectively.